Protective and Functional Coatings for Metallic and Ceramic Substrates (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This selection of ten papers, published in 2019 by researchers and institutions based in various countries around the world, allows an appreciation of the variety and significance of ongoing research in the wide field of protective and functional coatings. The most noteworthy investigations conducted in the area of surface protection are currently proceeding at a similar rapid pace in a twofold direction toward deeper and increasingly reliable knowledge of degradation and protection mechanisms as well as technological optimization of the selection and design of new materials, coating deposition processes, and characterization methods. This summarized collection serves as a representative essay of the collective worldwide efforts toward the development of more durable surfaces. Both organic and inorganic coatings are included among the protection strategies from a large variety of deposition processes, with interesting examples of organic-inorganic composites being proposed. Major attention is devoted to protection from both electrochemical and chemical corrosion of different metallic alloys and to advanced SiC-SiC composites exposed to the aggressive environments of gas turbines. Examples of modelling of wear corrosion examples are also reported. A dedicated space was intentionally devoted to the selection of papers detailing examples of the applicability of advanced characterization techniques. As an example of the wide field of research on innovative functional coatings, one study presents Mo alloys as an electrocatalytic material for the hydrogen evolution reaction. A comprehensive review of directed energy deposition additive manufacturing of metallic components completes this collection.